2015
DOI: 10.1037/ser0000050
|View full text |Cite
|
Sign up to set email alerts
|

The influence of military sexual trauma on returning OEF/OIF male veterans.

Abstract: Military sexual trauma (MST) encompasses experiences of sexual harassment and/or assault that occur during active duty military service. MST is associated with postdeployment mental health, interpersonal, and physical difficulties and appears to be more influential in the development of posttraumatic stress disorder (PTSD) than other active duty experiences, including combat, among women veterans. Although some literature suggests that men who experience MST also evidence significant postdeployment difficultie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 38 publications
(73 reference statements)
1
29
0
Order By: Relevance
“…Nearly 5% of male and more than 40% of female veterans in our study reported experiences of unwanted sexual contact during their military service; similar rates were found among a recent population-based sample of OEF/OIF veterans (Barth et al, 2016). Although these rates of MSA are higher than those previously reported among other population-based samples of veterans (Kang et al, 2005;Klingensmith, Tsai, Mota, Southwick, & Pietrzak, 2014;Street et al, 2008), they are within the ranges reported among samples derived from the VA health care system Fontana & Rosenheck, 1998;Hankin et al, 1999;Mondragon et al, 2015;Sadler et al, 2003;Surìs et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…Nearly 5% of male and more than 40% of female veterans in our study reported experiences of unwanted sexual contact during their military service; similar rates were found among a recent population-based sample of OEF/OIF veterans (Barth et al, 2016). Although these rates of MSA are higher than those previously reported among other population-based samples of veterans (Kang et al, 2005;Klingensmith, Tsai, Mota, Southwick, & Pietrzak, 2014;Street et al, 2008), they are within the ranges reported among samples derived from the VA health care system Fontana & Rosenheck, 1998;Hankin et al, 1999;Mondragon et al, 2015;Sadler et al, 2003;Surìs et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…Prior research has demonstrated that MST is associated with lower social support, decreased social functioning, familial dissatisfaction, and difficulties with intimate relationships and social readjustment. 12 15 Moreover, interpersonal processes have been implicated in suicidal ideation in other samples—as both risk and protective factors. For example, loneliness is associated with suicidal ideation, 16 whereas social support is inversely associated with suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…Among military veterans who sought care at a VA facility, men and women who had experienced MST had higher odds of posttraumatic stress disorder (PTSD), other anxiety disorders, and depression than veterans who were not victims of MST during their military career (Kimerling et al, 2010;Maguen et al, 2012). Research focusing specifically on male veterans has shown that men who experienced MST, or sexual assault specifically, self-reported a greater number of depression symptoms and were more likely to be diagnosed with a mood disorder than were men who had not had these experiences (Chang et al, 2003;Mondragon et al, 2015). Male victims, whether civilian or military, may experience suicidal ideation, and some may make a suicide attempt (Schry et al, 2015;Tiet, Finney, and Moos, 2006;Walker, Archer, and Davies, 2005).…”
Section: Mental Health Carementioning
confidence: 99%
“…Previous research showed that, among veterans who had been referred to a mental health clinic for anxiety, those who had experienced MST (1) perceived less support from those in their social network than those who had not experienced MST and (2) were more likely to indicate that they have been "shamed, embarrassed, or repeatedly told [they were] no good" ( Mondragon et al, 2015).…”
Section: Advocacy Social Support and Informationmentioning
confidence: 99%
See 1 more Smart Citation